Use of Aliphatic Carboxylic Acid Derivatives for NHC/Photoredox-Catalyzed meta-Selective Acylation of Electron-Rich Arenes - Goto, Yamato; Murakami, Sho; Sumida, Yuto; Ohmiya, Hirohisa (Synthesis, 2024)
We describe the use of acyl imidazoles derived from aliphatic carboxylic acids for the N-heterocyclic carbene/organic photoredox co-catalyzed meta-selective functionalization of electron-rich arenes. Compared to our previous work, a change of the wavelength of the applied LED light from 440 nm to 390 nm promotes this reaction efficiently.
Keywords: N-heterocyclic carbene; photoredox catalysis; meta-selectivity; acylation; arenes